Preparation method of high-adhesion hemostatic antibacterial degradable hydrogel based on irradiation crosslinking and hydrogel
The preparation of high adhesion hemostasis and antibacterial degradable hydrogels based on irradiation crosslinking has solved the problems of existing hemostasis hydrogel materials on the human body and the inability to biodegrade, and achieved rapid hemostasis, good biocompatibility and complete biodegradation effects.
Patent Information
- Application Number
- CN202411868606.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing hemostatic hydrogel materials are highly toxic to the human body and cannot be completely biodegradable. The preparation process is cumbersome, the operation is complicated, and the cost is high. It cannot effectively solve the problems of in vivo injuries and postoperative wound hemostasis.
High adhesion hemostasis and antibacterial degradable hydrogels were prepared by irradiation crosslinking. By dissolving polyvinyl alcohol and tannin acid in ethanol solution, trimethylolamide and lipoic acid were added, and after freeze-thawing and high-energy radiation treatment, a hydrogel with good bioadhesion characteristics and mechanical strength was formed.
The prepared hydrogel has the characteristics of rapid hemostasis, good biocompatibility and complete biodegradation. It can degrade safely in the body, overcome the problems of existing hydrogel materials toxicity and inability to biodegradation of humans, and has application value in the fields of antibacterial, anti-inflammatory, antioxidant, etc.
Smart Images

Figure CN119868625A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials, and particularly relates to a preparation method of a high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking and the hydrogel. Background Art
[0002] Frequent bleeding and oozing in damaged tissues, the body and trauma surgery make it difficult for wounds to heal, causing great trouble to human life and health. Physical methods such as sutures and staples to stop bleeding and the body's physiological hemostasis cannot achieve the effect of rapid hemostasis. Therefore, the use of other exogenous substances to accelerate hemostasis has received great attention and research. With the deepening of research on hemostatic materials, absorbable hemostatic materials have become a research focus. At present, the main absorbable hemostatic materials studied at home and abroad are gelatin, collagen, fibrin glue, oxidized cellulose, chitosan and sodium alginate, which can basically meet the hemostatic needs of general trauma, but the problem of hemostasis of internal injuries and postoperative wounds cannot be well solved. In addition, the existing absorbable hemostatic materials are still not ideal in matching the mechanical strength of tissues, and the preparation of hydrogels still requires more additives such as initiators and cross-linking agents, which is still a potential safety issue.
[0003] Hydrogels are highly water-containing three-dimensional network gels that are similar to and have the properties of natural extracellular matrix. They are widely used in the field of biomedical materials, such as wound dressings, cell culture, and tissue repair. Hydrogels are given tissue adhesion and can form covalent or non-covalent bonds with tissues to physically seal bleeding wounds and promote tissue repair. Adhesive hydrogels must not only have wet tissue adhesion, rapid hemostasis, and good biocompatibility, but also have strong mechanical strength and applicability to irregularly shaped target sites.
[0004] At present, existing hemostatic hydrogel materials are usually highly toxic to the human body and cannot be completely biodegraded. For example, CN201510155744.5 "A method for preparing chitosan-based hydrogel by high-energy ray irradiation" inevitably uses highly toxic solvents and additives such as acrylamide during the preparation process, which is not conducive to human wound healing, and its anti-inflammatory and antibacterial functions are not sufficient to meet the conditions for wound healing. In addition, the preparation process of existing hydrogels is cumbersome, the operation is relatively complicated, the cost is high, and it is not conducive to large-scale production and application. Summary of the invention
[0005] In order to obtain a new type of hemostatic hydrogel material, the present invention provides a method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking. The degradable hydrogel prepared by this method can quickly stop bleeding, has good controllable bioadhesion properties and mechanical strength, and has good biological activity and biocompatibility, and has application value in the fields of antibacterial, anti-inflammatory, antioxidant, and skin defect repair.
[0006] The invention also provides a high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking.
[0007] The present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, the preparation method comprising:
[0009] Dissolving polyvinyl alcohol and tannic acid together in an ethanol solution to obtain a mixed solution;
[0010] pouring the mixed solution into a mold, thawing it after freezing treatment to obtain a non-adhesive outer layer;
[0011] Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution;
[0012] Adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution;
[0013] The reaction solution is poured into the mold to cover the non-adhesive outer layer, and the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
[0014] Furthermore, the polyvinyl alcohol and tannic acid are dissolved in an ethanol solution to obtain a mixed solution, which specifically includes:
[0015] Dissolving polyvinyl alcohol in an ethanol solution at 80-90° C. to obtain a polyvinyl alcohol solution;
[0016] Adding tannic acid to the polyvinyl alcohol solution to dissolve it, thereby obtaining a mixed solution;
[0017] Wherein, the ethanol solution is obtained by mixing ethanol and water in a volume ratio of 1:1;
[0018] In the mixed solution, the mass fraction of polyvinyl alcohol is 1%-10%, and the mass fraction of tannic acid is 1%-10%.
[0019] Further, the mixed solution is poured into a mold, and thawed after freezing to obtain a non-adhesive outer layer, which specifically includes:
[0020] The mixed solution is poured into a mold, frozen at -20±5°C for 2±0.2h, and then thawed to obtain a non-adhesive outer layer.
[0021] Further, the step of adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution; and adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution specifically comprises:
[0022] Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution;
[0023] Adding lipoic acid to the Tris buffer mixed solution, and then stirring at 70±2° C. for 3±0.5 h to dissolve, to obtain a reaction solution;
[0024] In the reaction solution, the mass fraction of tris(hydroxymethyl)aminomethane is 1%-10%, and the mass fraction of lipoic acid is 5%-30%.
[0025] Further, the reaction solution is poured into the mold to cover the non-adhesive outer layer, and the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel, which specifically includes:
[0026] The reaction solution is poured into the mold to cover the non-adhesive outer layer, and then the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy for a time of 0.1 to 24 hours to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
[0027] Furthermore, the thickness of the non-adhesive outer layer is 1 to 10 mm, and the total thickness of the highly adhesive hemostatic and antibacterial degradable hydrogel is 2 to 20 mm.
[0028] Based on the same inventive concept, the present invention provides a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, and the hydrogel is prepared by the above-mentioned method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking.
[0029] Based on the same inventive concept, the present invention provides a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, wherein the hydrogel comprises an adhesive hydrogel inner layer and a non-adhesive hydrogel outer layer, and a continuous gradient transition layer between the adhesive hydrogel inner layer and the non-adhesive hydrogel outer layer;
[0030] The adhesive hydrogel inner layer comprises the following components by mass fraction:
[0031] Tannic acid <10%, tris(hydroxymethyl)aminomethane (Tris) 1%-10%, tannic acid grafted polylipoic acid 5%-30%, polyvinyl alcohol 1%-10%, ethanol solution 40%-92%;
[0032] The non-adhesive hydrogel outer layer comprises the following components by mass fraction:
[0033] Tannic acid 1%-10%, polyvinyl alcohol 1%-10%, ethanol solution 80%-98%.
[0034] Furthermore, the thickness of the inner layer of the adhesive hydrogel is 100-200 μm, and the thickness of the outer layer of the non-adhesive hydrogel is 100-200 μm.
[0035] Based on the same inventive concept, the present invention also provides a use of a high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking in the preparation of any one of hemostatic materials, hemostatic medical devices, antibacterial materials, anti-inflammatory materials, antioxidant materials and skin defect repair materials.
[0036] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0037] 1. The present invention discloses a method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking. The method enables the hydrogel to have mechanical properties that match the strength of tissues through radiation cross-linking. The prepared hydrogel can seal wounds through physical adhesion and form covalent or non-covalent bonds with the tissue interface to enhance the adhesion between the gel and the tissue interface. The hydrogel has good controllable bioadhesion properties and mechanical strength, can stop bleeding quickly, and has good biological activity and biocompatibility. The materials used can be completely biodegradable and have application value in the fields of antibacterial, anti-inflammatory, antioxidant, and skin defect repair. The hydrogel can be particularly used for preparing oral ulcer patches, and can also be used for wound closure and hemostasis in the body, and can be safely degraded in the body. The present invention overcomes the problems of adding toxic additives in the existing hydrogel preparation process and poor adhesion strength between the gel and the tissue interface.
[0038] 2. The present invention discloses a highly adhesive, hemostatic, antibacterial and degradable hydrogel based on radiation cross-linking. The hydrogel has a gradient structure, with a hydrogel containing polyvinyl alcohol and tannic acid as an outer layer, and a hydrogel containing tannic acid grafted polylipoic acid and polyvinyl alcohol as an adhesive inner layer. There is no obvious boundary between the inner and outer layers, and the internal networks interact with each other through multiple hydrogen bonds, with strong cohesion, tight bonding, and basically consistent mechanical strength, without delamination. In the stress-strain curve test, no interlayer cracking occurs; the inner layer of the hydrogel of the present invention has a high-strength wet tissue adhesion ability, and is used to adhere to the wound surface, effectively close the wound and resist bacteria, and accelerate wound healing; the outer layer has no adhesion, and is used to prevent adhesion of wounds in vitro and in vivo, and provides certain mechanical strength and antibacterial properties; the hydrogel of the present invention can achieve rapid wound closure treatment, and form a physical barrier to provide a good environment for wound healing, thereby providing a new method for accelerating wound healing.
[0039] 3. The present invention discloses a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking. The hydrogel is a highly adhesive hemostatic and antibacterial degradable hydrogel with a continuous gradient structure. The catechol active ingredient - tannic acid and lipoic acid with anti-inflammatory and antioxidant properties are directly added to polyvinyl alcohol. The obtained hydrogel has good controllable bioadhesion properties and mechanical strength. Compared with the traditional hemostatic and antibacterial degradable hydrogel system, the hydrogel of the present invention has excellent elasticity and mechanical properties and can be cut into various shapes according to needs. The preparation method of the hydrogel of the present invention is simple and the raw materials are easily available. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0041] Figure 1 These are photos of the hydrogel of the present invention: the left picture is a length measurement picture; the middle picture is a width measurement picture; and the right picture is an actual hydrogel rectangular spline.
[0042] Figure 2 The diagrams are microstructure diagrams of the hydrogels of the present invention: the left diagram is a microstructure diagram of a hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 3% polyvinyl alcohol, and a total tannic acid content of 3%; the middle diagram is a microstructure diagram of a hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 6% polyvinyl alcohol, and a total tannic acid content of 6%; the right diagram is a microstructure diagram of a hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 10% polyvinyl alcohol, and a total tannic acid content of 10%.
[0043] Figure 3 These are pictures showing the effects of the hydrogel of the present invention on hemostasis and tissue defect repair: the first picture on the left is a picture of mouse liver injury; the second picture on the left is a picture of the hydrogel attached to the liver injury wound to stop bleeding; the second picture on the right is a picture of the hydrogel attached to the mouse liver injury wound with no bleeding; the first picture on the right is a picture of the effect of the hydrogel on the repair of mouse liver injury wound. DETAILED DESCRIPTION
[0044] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0045] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0047] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0048] The technical principles of the present invention are as follows:
[0049] The present invention provides a method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, the preparation method comprising:
[0050] Dissolving polyvinyl alcohol and tannic acid together in an ethanol solution to obtain a mixed solution;
[0051] pouring the mixed solution into a mold, thawing it after freezing treatment to obtain a non-adhesive outer layer;
[0052] Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution;
[0053] Adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution;
[0054] The reaction solution is poured into the mold to cover the non-adhesive outer layer, and the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
[0055] In the present invention, after the mixed solution is poured into the mold, it is frozen and thawed. The freezing and thawing process is conducive to the physical cross-linking of the polyvinyl alcohol in the solution to form hydrogen bonds between polymer chains, so that it can be gelled and quickly formed.
[0056] In the present invention, the polyvinyl alcohol in the non-adhesive outer layer mainly functions to form a polymer network through radiation cross-linking to provide skeleton support; tannic acid is a catechol active ingredient, providing good antibacterial properties and biocompatibility.
[0057] In the present invention, the polyvinyl alcohol in the adhesive inner layer mainly provides skeleton support by forming a polymer network through radiation cross-linking; tannic acid is a catechol active ingredient, providing good antibacterial and biocompatibility; tris(hydroxymethyl)aminomethane mainly adjusts the pH of the solution to maintain it at around neutral; lipoic acid mainly provides strong wetting tissue adhesion and provides antibacterial and antioxidant properties.
[0058] In the present invention, after lipoic acid is added to the Tris buffer mixed solution to dissolve, the lipoic acid undergoes ring-opening polymerization to form polylipoic acid, and the reaction is continued to complete the grafting reaction of tannic acid and polylipoic acid.
[0059] In the present invention, the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy. Under irradiation, the polyvinyl alcohol in the hydrogel undergoes a cross-linking reaction to form a polymer network, further improving its mechanical properties. Under irradiation, the tannic acid-polylipoic acid network in the hydrogel undergoes a certain degree of irradiation degradation reaction, which, on the one hand, balances the cohesive force and the adhesive force in order to improve the overall adhesive strength, and on the other hand, exposes more adhesive groups in the adhesive layer to improve the adhesive strength.
[0060] Furthermore, the polyvinyl alcohol and tannic acid are dissolved in an ethanol solution to obtain a mixed solution, which specifically includes:
[0061] Dissolving polyvinyl alcohol in an ethanol solution at 80-90° C. to obtain a polyvinyl alcohol solution;
[0062] Adding tannic acid to the polyvinyl alcohol solution to dissolve it, thereby obtaining a mixed solution;
[0063] Wherein, the ethanol solution is obtained by mixing ethanol and water in a volume ratio of 1:1;
[0064] In the mixed solution, the mass fraction of polyvinyl alcohol is 1%-10%, and the mass fraction of tannic acid is 1%-10%.
[0065] In the present invention, the advantage of mixing ethanol and water in a volume ratio of 1:1 is that the solute-solvent interaction is utilized to avoid excessive viscosity of the solution, quickly dissolve polyvinyl alcohol and tannic acid, promote the dissolution of lipoic acid added later, and control the ring-opening polymerization of lipoic acid, wherein the role of ethanol is to induce the ring-opening polymerization of lipoic acid to form polylipoic acid.
[0066] Further, the step of adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution; and adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution specifically comprises:
[0067] Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution;
[0068] Adding lipoic acid to the Tris buffer mixed solution, and then stirring at 70±2° C. for 3±0.5 h to dissolve, to obtain a reaction solution;
[0069] In the reaction solution, the mass fraction of tris(hydroxymethyl)aminomethane is 1%-10%, and the mass fraction of lipoic acid is 5%-30%.
[0070] In the present invention, the benefit of adding tris(hydroxymethyl)aminomethane and lipoic acid to the mixed solution and then stirring at 70±2° C. for 3±0.5 h is that the polymerization degree of lipoic acid and the crosslinking degree of the tannic acid-polylipoic acid network can be regulated to obtain a hydrogel system with different adhesion strengths.
[0071] Further, the reaction solution is poured into the mold to cover the non-adhesive outer layer, and the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel, which specifically includes:
[0072] The reaction solution is poured into the mold to cover the non-adhesive outer layer, and then the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy for a time of 0.1 to 24 hours to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
[0073] In the present invention, the high-energy ray dose is 1 to 10 kGy, which can accurately control the irradiation dose on the one hand, and accurately regulate the mechanical strength and adhesion strength of the hydrogel on the other hand. The irradiation time is 0.1-24 hours, which is short and easy to operate, and the control is accurate, so that the reaction is complete.
[0074] Based on the same inventive concept, the present invention provides a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, wherein the hydrogel comprises an adhesive hydrogel inner layer and a non-adhesive hydrogel outer layer, and a continuous gradient transition layer between the adhesive hydrogel inner layer and the non-adhesive hydrogel outer layer;
[0075] The adhesive hydrogel inner layer comprises the following components by mass fraction:
[0076] Tannic acid 1%-10%, tris(hydroxymethyl)aminomethane (Tris) 1%-10%, tannic acid grafted polylipoic acid 5%-30%, polyvinyl alcohol 1%-10%, ethanol solution 40%-92%;
[0077] The non-adhesive hydrogel outer layer comprises the following components by mass fraction:
[0078] Tannic acid 1%-10%, polyvinyl alcohol 1%-10%, ethanol solution 80%-98%.
[0079] In the hydrogel of the present invention, the mass fraction of tannic acid is 1%-10%, which can accurately regulate the content of catechol in the hydrogel and its own antibacterial property, the mass fraction of Tris is 1%-10%, which has the advantage of accurately regulating the acidity and alkalinity of the hydrogel, the mass fraction of polyvinyl alcohol is 1%-10%, which accurately controls the content of polyvinyl alcohol polymer chains in the hydrogel, thereby controlling the mechanical strength of the hydrogel, and the benefit of 5%-30% of tannic acid grafted with polylipoic acid is that the cross-linking density of the polymer network inside the hydrogel is more accurately controlled. If the content of each component is too high or too low, it is not conducive to the gelation of the hydrogel, and the mechanical strength, adhesion strength, antibacterial property, etc. cannot reach the expected indicators.
[0080] The preparation method of the high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking of the present invention and the hydrogel will be described in detail below in combination with the examples and experimental data.
[0081] Example 1
[0082] This embodiment provides a method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, as follows:
[0083] 1) Disperse 2.4 g of polyvinyl alcohol in a mixed solvent of 17.6 mL of water and 17.6 mL of ethanol, and heat and stir at 90° C. for 1 h to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution with a mass fraction of 6%;
[0084] 2) dissolving 2.4 g of tannic acid (TA) in a 6% polyvinyl alcohol solution by mass, stirring to completely dissolve it, to obtain a 6% tannic acid polyvinyl alcohol solution A;
[0085] 3) pouring the tannic acid polyvinyl alcohol solution A into a mold, freezing it at -20°C for 2 hours, and then taking it out to completely thaw it to form a non-adhesive lower layer;
[0086] 4) Take another portion of tannic acid polyvinyl alcohol solution A, add 5 g Tris and 10 g lipoic acid (LA), heat at 70°C, stir vigorously (400 rpm) for 3 h, and cool (cooling rate 20°C / h) to room temperature to obtain solution B;
[0087] 5) pouring the solution B into the mold and covering the non-adhesive lower layer, followed by packaging;
[0088] 6) The hydrogel encapsulated in step 5) is subjected to a 5 kGy dose 60 The Co high-energy gamma ray was irradiated at room temperature for 8 hours. After the irradiation, the mold was removed to obtain a highly adhesive, hemostatic, antibacterial and degradable hydrogel.
[0089] The hydrogel prepared in Example 1 was used for hemostasis and tissue repair experiments on rat liver wounds.
[0090] The rats were placed in a supine position and anesthetized with a special anesthesia device. The abdomen was disinfected with 70% ethanol and the skin was prepared. The abdominal cavity was opened to find the right lobe of the liver and wrapped with sterile gauze. A wound with a diameter of 8 mm was made on the right lobe of the liver with a special mold. The adhesive hydrogel was spread on the wound and gently pressed. The hemostasis was observed and the blood was continuously absorbed with filter paper and collected in a specific test tube until there was no obvious rebleeding. The amount of bleeding was recorded. The hydrogel adhered to the liver wound was re-implanted into the rat's body together with the liver. The healing of the rat liver wound was observed and recorded 1 day, 3 days, and 7 days after re-implantation.
[0091] Figure 1 These are photos of the hydrogel of the present invention: the left picture is a length measurement picture; the middle picture is a width measurement picture; the right picture is: an actual hydrogel rectangular spline.
[0092] Figure 2 The microstructure diagram of the hydrogel of the present invention: the left, middle and right diagrams are respectively: the microstructure diagram of the hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 3% polyvinyl alcohol, and 3% tannic acid in total; the microstructure diagram of the hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 6% polyvinyl alcohol, and 6% tannic acid in total; the microstructure diagram of the hydrogel containing 5% tris(hydroxymethyl)aminomethane, 20% tannic acid grafted polylipoic acid, 10% polyvinyl alcohol, and 10% tannic acid in total. With the increase of the content of polyvinyl alcohol and tannic acid, the roughness in the micromorphology decreases, the polyvinyl alcohol content increases, the mechanical strength of the hydrogel increases, the cohesion increases, and the adhesion strength of the hydrogel decreases.
[0093] Figure 3 The effect diagram of the hydrogel of the present invention on hemostasis and tissue defect repair is shown below: The left picture shows a mouse liver injury; the left picture shows a hydrogel attached to a liver injury wound to stop bleeding; the right picture shows a hydrogel attached to a mouse liver injury wound without bleeding; the right picture shows a hydrogel on the mouse liver injury wound repair effect. The liver injury wound was made by mold, and the hydrogel adhesion hemostasis, wound closure and tissue repair effects were tested.
[0094] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0095] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0096] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, characterized in that: The preparation method comprises: Dissolving polyvinyl alcohol and tannic acid together in an ethanol solution to obtain a mixed solution; pouring the mixed solution into a mold, thawing it after freezing treatment to obtain a non-adhesive outer layer; Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution; Adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution; The reaction solution is poured into the mold to cover the non-adhesive outer layer, and the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
2. The method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 1, characterized in that: The step of dissolving polyvinyl alcohol and tannic acid in an ethanol solution to obtain a mixed solution specifically comprises: Dissolving polyvinyl alcohol in an ethanol solution at 80-90° C. to obtain a polyvinyl alcohol solution; Adding tannic acid to the polyvinyl alcohol solution to dissolve it, thereby obtaining a mixed solution; Wherein, the ethanol solution is obtained by mixing ethanol and water in a volume ratio of 1:1; In the mixed solution, the mass fraction of polyvinyl alcohol is 1%-10%, and the mass fraction of tannic acid is 1%-10%.
3. The method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 1, characterized in that: The mixed solution is poured into a mold, and thawed after freezing to obtain a non-adhesive outer layer, which specifically includes: The mixed solution is poured into a mold, frozen at -20±5°C for 2±0.2h, and then thawed to obtain a non-adhesive outer layer.
4. The method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 1, characterized in that: adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution; Adding lipoic acid to the Tris buffer mixed solution and fully dissolving it to obtain a reaction solution specifically comprises: Adding tris(hydroxymethyl)aminomethane to the mixed solution and dissolving it to obtain a Tris buffer mixed solution; Adding lipoic acid to the Tris buffer mixed solution, and then stirring at 70±2° C. for 3±0.5 h to dissolve, to obtain a reaction solution; In the reaction solution, the mass fraction of tris(hydroxymethyl)aminomethane is 1%-10%, and the mass fraction of lipoic acid is 5%-30%.
5. The method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 1, characterized in that: The step of pouring the reaction solution into the mold to cover the non-adhesive outer layer, and irradiating the solution in the mold with high-energy rays at a dose of 1 to 10 kGy to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel specifically comprises: The reaction solution is poured into the mold to cover the non-adhesive outer layer, and then the solution in the mold is irradiated with high-energy rays at a dose of 1 to 10 kGy for a time of 0.1 to 24 hours to obtain a highly adhesive hemostatic and antibacterial degradable hydrogel.
6. The method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 1, characterized in that: The thickness of the non-adhesive outer layer is 1 to 10 mm, and the total thickness of the highly-adhesive hemostatic and antibacterial degradable hydrogel is 2 to 20 mm.
7. A highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, characterized in that: The hydrogel is prepared by the method for preparing a highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to any one of claims 1 to 6.
8. A highly adhesive hemostatic and antibacterial degradable hydrogel based on radiation cross-linking, characterized in that: The hydrogel comprises an inner adhesive hydrogel layer and an outer non-adhesive hydrogel layer, and a continuous gradient transition layer is provided between the inner adhesive hydrogel layer and the outer non-adhesive hydrogel layer; The adhesive hydrogel inner layer comprises the following components by mass fraction: Tannic acid <10%, tris(hydroxymethyl)aminomethane 1%-10%, tannic acid grafted polylipoic acid 5%-30%, polyvinyl alcohol 1%-10%, ethanol solution 40%-92%; The non-adhesive hydrogel outer layer comprises the following components by mass fraction: Tannic acid 1%-10%, polyvinyl alcohol 1%-10%, ethanol solution 80%-98%.
9. The high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking according to claim 8, characterized in that: The thickness of the adhesive hydrogel inner layer is 100-200 μm, and the thickness of the non-adhesive hydrogel outer layer is 100-200 μm.
10. Use of a high-adhesion hemostatic and antibacterial degradable hydrogel based on radiation cross-linking as claimed in any one of claims 7 to 9 in the preparation of any one of hemostatic materials, hemostatic medical devices, antibacterial materials, anti-inflammatory materials, antioxidant materials and skin defect repair materials.
Citation Information
Patent Citations
Method for preparing chitosan-based hydrogel by virtue of high-energy ray radiation
CN104725567A
PH-sensitive block polymer, FRET (fluorescence resonance energy transfer) composite and their preparation methods
CN106117525A
Levofloxacin carbon quantum dot cross-linked hydrogel material as well as preparation method and application thereof
CN118319949A
Stretchable antibacterial hydrogel as well as preparation method and application thereof
CN118406261A
Use of an (r)-enantiomer of lipoic acid in cosmetics and dermatologicals
US20030180337A1
Cited By
Medical biogel of microbial fructan and preparation method of medical biogel
CN121490120A